Phyto - Transferosomes: Emerging Vesicular Nanocarriers for Topical Delivery of Phytoconstituents - Swami Shivlila; Sameer Shafi; Waghmare Pranita; Bhalke, Gadhave Ankita; Damane Madhuri; Giri, Dr.Mahendra A (Asian Journal of Pharmaceutical Research and Development, 2026)
Skin disorders, including psoriasis, acne, fungal infections, chronic wounds, photoaging, and skin cancer, are major global health concerns that often require long-term treatment. Phytoconstituents derived from medicinal plants possess significant antioxidant, anti-inflammatory, antimicrobial, wound-healing, and anticancer properties, making them attractive candidates for topical therapy. However, their clinical effectiveness is frequently limited by poor aqueous solubility, low stability, photodegradation, inadequate skin permeation, and reduced bioavailability. To overcome these challenges, nanotechnology-based vesicular carriers have been extensively explored. Among them, transferosomes have emerged as promising ultra-deformable lipid vesicles capable of enhancing drug penetration across the stratum corneum. Incorporation of phytoconstituents into transferosomal systems, known as phyto-transferosomes, offers improved encapsulation efficiency, protection against degradation, sustained drug release, and enhanced therapeutic efficacy. This review discusses skin anatomy and barriers to topical drug delivery, the role of phytoconstituents in dermatological therapy, fundamentals and mechanisms of transferosomes, formulation components, preparation methods, and characterization techniques. Furthermore, therapeutic applications, safety and regulatory considerations, patents, commercialization prospects, and future perspectives are highlighted. Overall, phyto-transferosomes represent a promising strategy for improving the topical delivery and clinical performance of herbal therapeutics.